PENANGGULANGAN TINDAK PIDANA PENIPUAN TERKAIT DENGAN TRANSAKSI TRANSFER DANA PADA SEKTOR PERBANKAN - Ratnawati, Theresia Endang (Wacana Hukum, 2013)
Abstrak: Fraudulent acts have caused many casualties bank customers. therefore necessary laws to protect customer responsive acting in good faith. With the issuance of Law No. 8/2010, the bank actually had a legal basis to delay the transaction. Transaction delay is an act of financial services providers to not carry out transactions on their own initiative, or upon order of the investigator, the prosecutor and the judge’s order. By Law No. 8/2010, the bank can delay the transaction and refund the remaining funds to customers who become victims of fraud to protect consumers acting in good faith. Key words: transfer of funds, bank.